Using Molecular Methods to Identify and Monitor Xenobiotic-Degrading Genes for Bioremediation - Fuller, Edward (2021)
Environmental pollution is a matter of increasing concern worldwide, for which new and innovative solutions are constantly required. Bioremediation, the transformation of contaminants into less toxic substances using microorganisms, can provide an economically viable and ecologically friendly method of removing these pollutants. The identification of the microorganisms capable of degradation and their degradative genes is typically the first and most important step, when bioremediation of a new compound is devised. Once known, the gene encoding the degradative enzyme can be used to confer the degradative ability to either the indigenous microbial population or to ‘non-native’ genetically modified microorganisms. Furthermore, the identification of the genes can also allow for the presence and activity of degradative organisms to be monitored in order to adequately follow and predict the outcome of a bioremediation process. Traditional microbiological methods have been used for this purpose for several decades. Nonetheless, recent advances in molecular biology are allowing increasingly accurate and informative techniques to be applied. This review provides an overview of the genetic methods used to identify degradative genes, with an emphasis on pesticides, and their application in relation to gene monitoring in a bioremediation setting.